Modelación de la Accesibilidad en ArcView 3: Una extensión para calcular el tiempo de viaje y obtener información sobre captación de mercados - Farrow, Andrew; Nelson, A. (International Center for Tropical Agriculture, 2001)
CIAT programmed this simple and flexible GIS tool to automate the creation of accessibility surfaces. Previously, these surfaces were laboriously created, step-by-step, using ArcINFO software from the Environmental Systems Research Institute (ESRI). You can install the Accessibility Analyst if you have the ESRI ArcView 3 software and its ArcView Spatial Analyst. From this page, you can download the extension and documentation, see case studies of the extension at work, and follow up links with other people working in the same field. CIAT donors generously funded the development of Accessibility Analyst, in particular, the Ecoregional Fund to Support Methodological Initiatives (managed by the International Service for National Agricultural Research); Environmental Economics and Indicators Unit of the World Bank; and the Regional Office for Latin America and the Caribbean of the United Nations Environment Programme.